2009
DOI: 10.1038/aps.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypoxic effect of ginsenoside Rbl on neonatal rat cardiomyocytes is mediated through the specific activation of glucose transporter-4 ex vivo

Abstract: Aim:The aim of this study was to investigate whether Gs-Rbl relieves the CoCl 2 -induced apoptosis of hypoxic neonatal rat cardiomyocytes and in which the role of glucose transporter-4 (GLUT-4). Methods: 10, 50, 100, 200, 400, and 500 µmol/L), adenine 9-β-D-arabinofuranoside (ara A, 500 µmol/L; AMPK inhibitor) and wortmannin (0.5 µmol/L; PI3K inhibitor) only in combination with 200 µmol/L Gs-Rbl were administered in hypoxic cardiomyocytes, which were induced by 500 µmol/L CoCl 2 for 12 h. Then, the apoptotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
(47 reference statements)
3
18
0
Order By: Relevance
“…Our previous study demonstrated that Gs-Rb1, by improving glucose uptake, plays an important role in protecting neonatal rat cardiomyocytes from CoCl 2 -induced apoptosis ex vivo [5] . This role may be controlled by the translocation of GLUT-4 mediated by both AMPK and/or PI3K signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study demonstrated that Gs-Rb1, by improving glucose uptake, plays an important role in protecting neonatal rat cardiomyocytes from CoCl 2 -induced apoptosis ex vivo [5] . This role may be controlled by the translocation of GLUT-4 mediated by both AMPK and/or PI3K signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous study [5] , cardiomyocyte cultures were prepared from hearts of 1-3-d-old rats. In brief, ventricles had been separated and cut into 1 mm 3 pieces and digested (37 ºC, 10 min, two to three such cycles to achieve full digestion) with phosphate-buffered saline (PBS) containing 0.08% trypsin and 0.05% collagenase II (Gibco).…”
Section: Cardiomyocytes Culturementioning
confidence: 99%
See 3 more Smart Citations